Rapid dislocation-mediated solute repartitioning towards strain-aging hardening in a fine-grained dilute magnesium alloy - Zhen-Ming Hua; Min Zha; Zhao-Yuan Meng; Shen-Bao Jin; Gang Sha; Tian-Shuai Wang; Cheng Wang; Hai-Long Jia; Yipeng Gao; Hui-Yuan Wang (Materials Research Letters, 2022)
Achieving appreciable strain-aging hardening coupling with fine-grain strengthening remains a critical challenge in dilute Mg alloys, as high-temperature solid-solution, utilized to impart high-level solutes for strain-aging, inevitably causes grain coarsening and great strength loss. Herein, we report a rapid dislocation-mediated solute repartitioning behavior upon aging in a low-temperature annealed Mg–1.0Zn–0.45Ca–0.33Sn–0.2Mn (wt.%) alloy. Thereby, appreciable strain-aging hardening (YS increment of ∼30 MPa) coupling with fine-grain (grain size of ∼2.5 µm) strengthening accounts for a high yield strength (∼297 MPa) and ductility (∼20%). It suggests a feasible avenue to develop strong dilute Mg alloys by combining strain-aging hardening and fine-grain strengthening.